Flux lattice melting and dimensional crossover in Bi-2212 single crystals - Kes, P.H. (1996)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Leiden University; Países Bajos